Cathodic Kinetics on Platinum and Stainless Steel in NaOH Environments. Issue 7 (21st July 2021) - Katona, R. M.; Carpenter, J.; Schindelholz, E. J.; Schaller, R. F.; Kelly, R. G.
Abstract : During typical atmospheric conditions, cathodic reduction reactions produce hydroxyl ions increasing the pH in the cathodic region. Therefore, cathodic reduction reactions are investigated on platinum and stainless steel 304 L (SS304L) in NaOH solutions ranging in pH from 13.6 to 16.5. It was found that in solution pHs less than 16.5 the cathodic reduction reaction on Pt and SS304L was ORR with an electron transfer number less than two due to superoxide formation as an intermediate. Increasing pH decreased the number of electrons transferred. At a pH of 16.5, the cathodic reduction reaction on SS304L is no longer ORR and the cathodic current on the surface of the alloy is due to oxide reduction occurring on the surface as indicated by the creation of multi-component Pourbaix diagrams. The results of this study have important implications for predicting corrosion in atmospheric environments.